2022
DOI: 10.1155/2022/4420870
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Embedded Smart Wearable Device Monitoring in Joint Cartilage Injury and Rehabilitation Training

Abstract: Joint injuries cause varying degrees of damage to joint cartilage. The purpose of this paper is to study the application of embedded smart wearable device monitoring in articular cartilage injury and rehabilitation training. This paper studies what an embedded system is and what a smart wearable device is and also introduces the rehabilitation training method of articular cartilage injury. We cited an embedded matching cost algorithm and an improved AD-Census. The joint cartilage damage and rehabilitation trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%